SUSTAINABLE HARVESTING OF TERMINALIA ARJUNA (ARJUNA) AND LITSEA GLUTINOSA (MAIDA) BARK IN CENTRAL INDIA - Pandey, A.; Mandal, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Terminalia arjuna (Arjuna) is a well-known medicinal plant whose bark is extensively used in ayurvedic medicine, particularly as cardiac tonic. Demand for Arjuna bark, both in India and abroad has been growing rapidly for over a decade. Litsea chinensis (Maida) is a medium sized tree. Its bark is used to treat joint pain, fracture, sprain, arthritis, back pain, indigestion, cough and dryness of skin. Presently the bark of Arjuna and Maida is being extracted through unscientific and destructive harvesting practices. This is the first study on development of sustainable harvesting practices of Arjuna and Maida bark. The study revealed that the regeneration of bark in young trees was faster in comparison to old trees. In Arjuna, the bark was regenerated in two years whereas in Maida it took only one year. The study also showed that the stage of bark recovery (regrowth) varied from tree to tree, age of tree, harvesting technique (e.g. blaze making) and factors like temperature, relative humidity and time of stripping influenced wound healing in Arjuna and Maida. In Arjuna, the quality of trunk bark was superior in comparison to bark of other plant parts (stem, twigs) whereas no significant difference was found in Maida. Thickness of Arjuna bark at breast height varied from 8.12 to 20.96 cm and was found to be irrespective of the age/girth of tree. The medium aged trees gave better quality of bark. The best time to harvest bark was found between December and March. The study recommends that for sustainable harvest, only ¼ or 1/3 of the mature bark of total girth of the tree should be stripped by removing only outer and middle bark leaving the inner bark for regeneration from opposite quarters of the trunk. Thus sustainable bark harvesting can be done after every two years (In Arjuna) and one year (In Maida) by removing opposing quarters of trunk bark rather than girdling the trees.